A hacked kitchen scale-based system for quantification of grip strength in rodents. (May 2022) - Homolak, Jan; Virag, Davor; Kodvanj, Ivan; Matak, Ivica; Babic Perhoc, Ana; Knezovic, Ana; Osmanovic Barilar, Jelena; Trkulja, Vladimir; Salkovic-Petrisic, Melita
Abstract: Background: Assessment of neuromuscular function is critical for understanding pathophysiological changes related to motor system dysfunction in many rodent disease models. Among methods used for quantification of grip performance in rodents, gauge-based grip strength meters provide the most reliable results, however, such instruments are unaffordable by many laboratories. The present aim was to demonstrate how to build a rodent grip strength apparatus from scratch using a digital kitchen scale, an empty cage, and a microcontroller, with both hardware and software being completely open-source to enable maximal modularity and flexibility of the instrument in concordance with the principles of open-source bioinstrumentation. Methods: NodeMCU ESP-32S was connected to a hacked digital kitchen scale-based platform and load cell data were acquired using custom open-source scripts. Data were analyzed in R using semi-automatic analysis algorithms implemented in the ratPASTA package. griPASTA system was tested by quantifying muscular rigidity in the rat model of Parkinson's disease (PD) induced by bilateral intrastriatal administration of 6-hydroxydopamine (6-OHDA). Results: In contrast to commercial instruments, the flexibility and modularity of the proposed platform enable collecting raw data and controlling for potential confounding effects on the grip strength. Muscular rigidity is significantly increased in the rat model of PD regardless of the dose used or reboxetine pretreatment. Neither trial speed nor animal weight was recognized as an important confounder. Conclusions: griPASTA provides a cheap, easy, precise, and reliable way to measure grip strength in rodents using widely available equipment and open-source software. Highlights: griPASTA is simple, reliable and open-source solution for measuring rodent grip strength. griPASTA can provide data related to potential confounders in animal experiments. Muscular rigidity is increased in 6-OHDA-induced rat model of Parkinson's disease.